Fast NO2 gas pollutant removal using CNTs/TiO2/CuO/zeolite nanocomposites at the room temperature - Ghobad Behzadi pour; Elahe Shajee nia; Elham Darabi; Leila Fekri aval; Hamed Nazarpour-Fard; Ehsan Kianfar (Case Studies in Chemical and Environmental Engineering, 2023)
In this study, fast gas adsorbent nanocomposites based on the carbon nanotubes (CNTs)/titanium dioxide (TiO2)/copper oxide (CuO)/Zeolite (CNTs/TiO2/CuO/Zeolite) and CNTs/TiO2 structures for nitrogen dioxide (NO2) gas removal have been investigated. The nanocomposite adsorbent films were deposited on the glass substrate using the push coating method. The nanocomposite films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET). The BET test was carried out to study the total surface and the diameter of the pores within the matrices of the nanocomposites. For the CNTs/TiO2 nanocomposite, the NO2 gas concentration (NGC) was decreased from 102 ppm to 41 ppm, and for the CNTs/TiO2/CuO/Zeolite nanocomposite NGC was decreased from 172 ppm to 34 ppm. The gas test results revealed that the efficiency and adsorption capacity of CNTs/TiO2/CuO/Zeolite nanocomposite were 80 % and 138 mg g−1, respectively with the NO2 reduction rate of K = 0.37 min−1. The additional gas test exhibited that the adsorption efficiency of the CNTs/TiO2/CuO/Zeolite nanocomposite is higher than that of CNTs/TiO2. This study is promising and opens new insight for investigating the adsorption capability of these materials for removal of the pollutants from industrial regions as environmentally friendly filters.